Methods of portraiture in the story of B. Mazikhov "It's time for leaf fall" - Ruslan Kh. Urusov; Rimma A. Shetova (Кавказология, 2022)
In the proposed article, based on the material of the story of Kabardian prose writer B. Mazikhov “It’s Time for leaf Fall”, techniques for depicting the appearance of heroes are considered. This article proves the manner of portraiture plays an important role in the transmission of one of the end-to-end ideas of the story. In a small volume of the work, there is a variety of means of depicting the appearance and spiritual world of the characters, the author’s penchant for pictorial laconism becomes obvious. In the usual techniques for transmitting an external impression, including different points of view, a technique conventionally designated as “erasure of features” plays the image of individual or progressively increasing details. It is characteristic that the greatest semantic load falls on the images drawn with the greatest completeness. The relevance of the presented work is because the work of B. Mazikhov currently remains both in terms of his poetics and the concept of the personality represented in it.